A SOLUTION TO THE DIFFICULTY OF VOCABULARY MASTERY TROUGH MEMRISE - Muh Felix Agung Cahyono; Hesty Puspita Sari; Yusniarsi Primasari (Universitas Islam Balitar, 2023)
The purpose of conducting research on the effectiveness of the Memrise application is to improve students' English vocabulary skills. Research on the effectiveness of this application has been carried out at MAN 3 BLITAR which is located in Blitar Regency. The method used in this study is a quantitative method by providing pre-test and post-test Memrise applications. This application will compare students who use the application with those who do not. The results of research on the effectiveness of this application are shown from the results of the post-test. The results of the post test at Man 3 Blitar still show a low average value, the data shows the number 47.77. This value shows that it is still far from the KKM score, which is 75.00. after using the memrise application in learning there is a significant increase in value, namely 85.00. It can be seen that the memrise application plays a role in increasing teacher knowledge, especially in terms of increasing students' English vocabulary skills.